MENINGKATKAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) DI KELAS VIII A SMP NEGERI 14 BANJARMASIN - Syarifah Alfisyah (Universitas Lambung Mangkurat, 2013)
The study background is based on the social study subject condition in State Junior School 14 of third class students “A” Banjarmasin showing that the students’ achievment is low and does not reach the minimal completeness of study determined by school, namely 78. This study used action research method. Indeed, the research also used two cycles and every cycles contains two meetings. The data collection here uses observation whether for teacher’ activity or students’ activity, written test, and questionaire for students. The result is concluded that (1) the students’ achievment undergo progress of minimal completeness of study, namely 90,80; (2) students’ activity using STAD undergo progres; and (3) the students’ respond toward the use of STAD show that the students are interested in implimenting STAD. In a word, the teachers are hoped to use STAD as the alternative to increase the students’ achievment so that the students are interested in learning.Keywords: Activity, Achievment, Social Study Subject, and STAD Model